Menstrual hygiene management in flood-affected Pakistan: Addressing challenges and ensuring women's health and dignity - Tufail, Zarnab; Ahmer, Wania; Gulzar, Shanza; Hasanain, Muhammad; Shah, Hussain Haider (Frontiers in Global Women's Health, 2023)
Pakistan's recent floods have worsened women's and girls' menstrual hygiene problems, compromising their health, dignity, and well-being. Supply chain issues, poor facilities, and cultural stigma limit menstrual products and hygiene management. Gender-sensitive disaster management and menstrual health education programmes can help. The Minimum Initial Service Package (MISP) can provide emergency reproductive health services. Involving men, working with religious leaders, and pre-disaster planning for menstrual hygiene management can help break the taboo and increase access to resources. Meeting ongoing needs requires timely menstrual hygiene product distribution, restocking, and renewal. By addressing these issues, Pakistan can empower post-flood women and girls through economic opportunities and legal protection.